Designing Bkd Website Based In Industrial Engineering Department Of Universitas Pembangunan Nasional “Veteran” Jawa Timur - Dwi Sukma Donoriyanto; Tranggono Tranggono; M. Wildan Kautsar (International Journal of Eco-Innovation in Science and Engineering, 2020)
Lecturer Workload (BKD) is a portrait of the lecturer workload in the implementation of University’s Tri Dharma in the next semester. In college academic activities, the reporting of Lecturer Workload (BKD) is important because it is concerned with the productivity of lecturer’s performance. The lecturer workload is commensurate with a minimum of 12 credits and a maximum of 16 credits in each semester in accordance with academic qualifications. The Department of Industrial Engineering of UPN “Veteran” Jawa Timur has implemented a manual lecturer workload reporting system and indirectly the high potential obstacles to the evaluation process. So that in its application Lecturer Workload reporting (BKD) must be able to facilitate between lecturers, assessors and head of department in coordination. This research aims to produce Lecturer Workload Information System (BKD) effectively and efficiently. The design of this system uses the System Development Life Cycle (SDLC) method. From the results obtained, the output of this system is that lecturers report their performance online, assessors can verify files easily, and study programs can monitor lecturers' performance. It is hoped that the Lecturer Workload Information System (BKD) can help the Industrial Engineering Study Program of the East Java National Veterans Development University in conducting the lecturer workload reporting process (BKD)